In silico detection of polymorphic microsatellites in the endangered Isis tamarind, Alectryon ramiflorus (Sapindaceae). (15th November 2018) - Nichols, Joel; Conroy, Gabriel C.; Kasinadhuni, Naga; Lamont, Robert W.; Ogbourne, Steven M.
Abstract : Premise of the Study: Alectryon ramiflorus (Sapindaceae) is an endangered rainforest tree known from only two populations. In this study, we identified polymorphic microsatellites, in silico, improving the effectiveness and efficiency of microsatellite development of nonmodel species. The development of genetic markers will support future conservation management of the species. Methods and Results: We used next‐generation sequencing and bioinformatics to detect polymorphic microsatellites, in silico, reducing both the time and cost of marker development. A panel of 15 microsatellites, 12 of which were polymorphic, were subsequently characterized in 64 adult trees representing the entire species range. Mean observed heterozygosity and expected heterozygosity were 0.471 and 0.425, respectively. The polymorphism information content across loci ranged from 0.152 to 0.875. Conclusions: The microsatellite markers developed in this study will be useful in gaining an understanding of A. ramiflorus ' genetic diversity, level of inbreeding, and population structure and for guiding future restoration and management efforts.